Visual acuity in high astigmatic eyes in Salta, Argentina - Danza, Rubén D. (2024)
Purpose: To identify factors that affect uncorrected visual acuity (UCVA) in highly astigmatic eyes. Methods: This clinical study was performed at an Ophthalmology Clinic in the Northwest region of Argentina. The study population consisted of all consecutive patients, aged between 10 and 40 years, with bilateral astigmatism higher than 2 dioptres (D) in at least one eye. The protocol included the following tests: UCVA, pinhole VA, best-corrected VA (BCVA), keratometry, scotopic pupil diameter measurement, subjective refraction, and objective refraction with cycloplegia. Results: A total of 405 patients were included in the study. Their mean age was 22.04 ± 10.62 years and 52.3% were female (n=212). The mean SE was -1.53 ± 1.79 D and the mean scotopic pupil was 5.4 ± 0.3 mm. In multiple linear logistic regression analysis, excluding amblyopes, worse pinhole VA (Odds ratio [OR]: 8.19, 95% confidence intervals [CI]: 4.76 to 14.07; p<0,001) and higher scotopic pupil size were significantly associated with worse UCVA. The presence of amblyopia was associated with higher pupillary diameter (OR: 4.37; 95% CI: 1.60 to 11.97; p=0.004). Conclusions: Our study revealed that pupil size affects UCVA in the astigmatic eyes of subjects living in a rural environment. Thus, further studies are necessary to understand if the correction of astigmatism should take in consideration pupil size, pinhole VA, and UCVA.